2005
DOI: 10.1074/jbc.m414413200
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Comparison of BMP-2, ProBMP-2, and the Free Pro-peptide Reveals Stabilization of the Pro-peptide by the Mature Growth Factor

Abstract: Pro-forms of growth factors have received intensive scientific attention recently because in some cases different biological activities have been ascribed compared with the mature growth factors. Examples are the pro-apoptotic role of the nerve growth factor (NGF) proform (proNGF) or the latency of the transforming growth factor (TGF)-␤ pro-form (proTGF-␤). To investigate a possible biological function of the pro-form of bone morphogenetic protein (BMP)-2, a member of the TGF-␤ family, mature BMP-2, proBMP-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 35 publications
1
60
1
Order By: Relevance
“…Interestingly, clustering was found between total bone, percentage of: bone marrow, trabeculae, cortex and total bone to elevated phosphorylation levels J Bolander et al BMP-and CaP-induced -release to cause a decrease in pH, providing a more soluble environment for the BMP (Hillger et al, 2005;Kamp et al, 1998). Alternatively, the release of Ca 2+ may mediate the subsequent release and biological availability of BMPs bound to the CaP-granules through hydrogen/ionic/electrostatic/hydrophobic interactions (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, clustering was found between total bone, percentage of: bone marrow, trabeculae, cortex and total bone to elevated phosphorylation levels J Bolander et al BMP-and CaP-induced -release to cause a decrease in pH, providing a more soluble environment for the BMP (Hillger et al, 2005;Kamp et al, 1998). Alternatively, the release of Ca 2+ may mediate the subsequent release and biological availability of BMPs bound to the CaP-granules through hydrogen/ionic/electrostatic/hydrophobic interactions (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For 3D analysis of in vivo formed bone, explants were analysed using the Phoenix NanoTom S nanoCT system, (GE Measurement and Control Solutions, Wunstorf, DE) with a 180 kV/15 W high-performance nanofocus X-ray tube as previously described (Kerckhofs et al, 2013). Briefly, the system was equipped with a tungsten target and was operated at a voltage of 60 kV and a current of 200 µA.…”
Section: Quantification Of De Novo Formed Bone By Nanoctmentioning
confidence: 99%
“…These interactions are supplemented by a network of charged/polar interactions. The side chain carboxylate of Glu 45 is in contact with Arg 14 and Lys B100 and His B71 of the second monomer; Arg 14 in turn contacts the side chain of Gln 43 and the main chain carbonyl oxygen of Tyr…”
Section: In Vitro Folded Full-length Spätzle Isoforms Are Stable Protmentioning
confidence: 99%
“…It has also been reported that propeptides guide the assembly of subunits into active protein complexes as in the case of the von Willebrand factor or caspase-3 (Wise et al 1988;Feeney and Clark 2005). The pro-peptides of TGF-b and very likely also bone morphogenetic proteins retard the biological activities of the mature growth factors (Böttinger et al 1996;Degnin et al 2004;Hillger et al 2005). While for some pro-peptides their biological activities are displayed even when they are not covalently linked to their mature parts (Gray and Mason 1990), in the case of NGF, the propeptide has to be covalently linked to the mature part to promote oxidative structure formation (Rattenholl et al 2001a).…”
mentioning
confidence: 99%